Status and long-term changes of coral reefs around Zanzibar - Ussi, Ali M.; Mohammed, Mohammed S.; Rashid, Rashid J.; Sheikh, Mohammed A.; Staehr, Peter A.; Muhando, Christopher A.; Yahya, Saleh; Dahl, Karsten (Frontiers in Marine Science, 2024)
Introduction Coral reefs as key ecosystems in Zanzibar are exposed to several anthropogenic and natural stressors. Methods The benthic composition and coverage of coral reefs were investigated on three data sets involving ten coral reefs monitored from 1992 to 2016. Firstly, we investigated differences in the reef composition using data from seven reefs in 2015. Secondly, we analyzed communities on three distinctive reefs (2010 to 2012) to understand the importance of seasons and reef zones (slope, crest and flat) on species abundance. Finally, we investigated long-term changes (1992 to 2016) of five reefs. Results Branching Porites and Acropora, and soft coral order Corallimorpharia, characterized sheltered reef communities. Soft corals and algal species characterized the reef communities exposed to strong hydrodynamic conditions, which also displayed greater cover of rocks and rubbles. The average dissimilarity between reefs ranged between 60% and 75%. The seasonal changes in community structure for reefs near Stone Town were mostly associated with soft coral Corallimorpharia. Indeed, the bare rock and algae distinguished the northern exposed reef from more sheltered reefs. Acropora was a key genus for the sheltered Chumbe reef, which explained between 14% and 18% of the dissimilarities among the three reefs. Hard corals covered between 40% and 70% in most years, with severe declines following El Niño events in 1998 and 2016. The dominating genus Acropora showed a strong decline from the late 1990s’ with signs of recovery at remote reefs compared to reefs closer to human residence. Discussion Our results highlight the importance of seasonality and spatial differences, reflecting differences in human impact and physical exposure and significant long-term changes in coral communities. Continued monitoring of reef health is essential to evaluate the success of ongoing management to sustain the reef services.